The undiagnosed rare disease clinic program of Indiana University School of Medicine: lessons learned from the first 100 cases enrolled (Phase-I pilot) - Khurram Liaqat; Rachel Hart; Marco Abreu; Kevin Booth; Amy Breman; Yann Gibert; Brett H. Graham; Benjamin M. Helm; Reynold C. Ly; Lili Mantcheva; Tae-Hwi L. Schwantes-An; Marwan K. Tayeh; et al. (Orphanet Journal of Rare Diseases, 2026)
Abstract Background The Undiagnosed Rare Disease Clinic (URDC) of Indiana University, established in January 2020, is a multidisciplinary collaborative clinic that focuses on providing genetic diagnoses for patients and families dealing with the uncertainty of an undiagnosed rare disease and/or diagnostic odyssey. Methods To identify rare disease-causing variants underlying the suspected undiagnosed genetic conditions in our patient cohort, the URDC team implemented the following procedure. After sequencing, each case was evaluated by a small multidisciplinary team using an individualized, multi-modal pipeline, incorporating a customized AI-based variant-prioritization system. Candidate genes and variants identified through this process were further assessed through targeted functional studies, including 3D structural modeling, RNA-seq and additional in vivo and in vitro assays. Results The patients enrolled in URDC were referred from both urban (80%) and rural (20%) communities, through various specialty services within Indiana University Health. Multi-site collaborations with research and clinical groups were established to inform the differential and to study the functional effects of gene/variant candidates. Cases were solved in a variety of ways, including exome reanalysis and RNA-seq, novel gene discovery and GeneMatcher collaborations, variant reclassification, periodic genome sequencing reanalysis, and phenotypic expansion. Of the initial 100 cases, 19 received a diagnosis and are considered “solved” and 6 cases are “possibly solved,” i.e., the result has a high likelihood of explaining the symptoms; 74 cases remain unsolved, and 1 case was withdrawn. Medical management changes positively impacted care in 7 patients with newly identified diagnoses. Conclusion The impact of the URDC on the resolution of rare disease diagnostic odysseys for people in Indiana, a state that has faced significant gaps in access to genetic services, is substantial. The URDC successfully resolved approximately 20% of the first 100 cases and presents a model that can be integrated in other institutions across the country. The remaining undiagnosed patients, and those who will be enrolled in the future, present a unique opportunity for further research and novel gene discovery.